Measuring the Impacts of Self Efficacy and Perceived Health Benefits toward Smoking Cessation of e-Cigarettes - Dewi, Berlinda Devi Liliyana (APPS Publications, 2022)
Smoking is one of the most preventable causes of disease and death, including cancer. This study aimed to investigate whether perceived health benefits and self-efficacy affects e-smoking cessation. The method used in this research is quantitative using an online survey started in November 2020. From 50 distributed questionnaires using Google Form link, only 34 responses are valid. The results reveal that self-efficacy, not perceived health benefits, had a significant influence on intention to quit smoking. This study extends our understanding of this relationship by highlighting the non-significant result in the health benefits–smoking cessation linkage.